2019
DOI: 10.1177/1046496419874877
|View full text |Cite
|
Sign up to set email alerts
|

The Authenticity of the Others: How Teammates’ Authenticity Relates to Our Well-Being

Abstract: Although prior research has linked being authentic to individual well-being, little is known about authenticity’s external effects, that is, whether being around those who are authentic is good or bad for us. Integrating authenticity research and social penetration theory, we propose that others’ authenticity facilitates a number of positive intra- and interpersonal processes. Using a sample of 715 employees nested in 109 teams working for a nonprofit organization, we found that teammate authenticity relates p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 113 publications
0
12
0
1
Order By: Relevance
“…For instance, Kernis and Goldman (2006) found that misunderstandings and conflict with others are linked to inauthenticity (Sedikides et al, 2019). Alternatively, work teammates can influence authenticity (Emmerich et al, 2020). For…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Kernis and Goldman (2006) found that misunderstandings and conflict with others are linked to inauthenticity (Sedikides et al, 2019). Alternatively, work teammates can influence authenticity (Emmerich et al, 2020). For…”
Section: Discussionmentioning
confidence: 99%
“…Luhmann, 1964a, S. 324, 380ff. ;1965, S. 173;Emmerich et al, 2019). 5 Unter Bedingungen hoher Mobilität der (potenziellen) Mitglieder erscheint die Entfremdungsthematik für die Organisation letztlich als Motivations-und Personalproblem, als Problem der Unzufriedenheit und Arbeitsleistungsminderung, als Behinderung der Beteiligung an formalen Situationen (vgl.…”
Section: Informaleunclassified
“…Additionally, employees who feel able to exhibit their true emotions and whose outward expression is thus aligned with their true self should also benefit from establishing meaningful connections with their coworkers, giving them access to the resources the group offers (Emmerich, Knoll, & Rigotti, 2020). For example, employees who share their struggles concerning a specific work task with their coworkers should receive help from them, constituting additional resources that protect their health (Hobfoll, 2002).…”
Section: Pca and Employee Healthmentioning
confidence: 99%
“…Specifically, expressing felt emotions, such as sadness, frustration and joy, enables employees to conserve and replenish the attentional and energy resources they would normally invest into monitoring and regulating said emotions (Baumeister et al, 1998;Baumeister et al, 2007;Muraven et al, 2006) and thus represents a self-regulatory break (Grandey et al, 2013). Additionally, employees who feel able to exhibit their true emotions and whose outward expression is thus aligned with their true self should also benefit from establishing meaningful connections with their coworkers, giving them access to the resources the group offers (Emmerich et al, 2020). For example, employees who share their struggles concerning a specific work task with their coworkers should receive help from them, constituting additional resources that protect their health (Hobfoll, 2002).…”
Section: Pca and Employee Healthmentioning
confidence: 99%
See 1 more Smart Citation